Evaluation of the Effectiveness of Professional Activisation Forms in Poland – Regression Discontinuity Design - Beata BIESZK-STOLORZ; Krzysztof DMYTROW (Communications of International Proceedings, 2020)
Expenditures connected with conducting active labour market policy force the necessity of conducting research on effectiveness of applied instruments and conducting evaluation studies. The aim of the article is to assess the impact of changes in the calculation methodology on cost and employment effectiveness of basic forms of professional activisation. These changes were introduced in 2015 and concerned two aspects: the definition of the end of participation in activisation and the definition of employment. In the analysis one of the basic counterfactual methods was used - the method of regression discontinuity design. The study was conducted on the basis of statistical data published by the Ministry of Family, Labour and Social Policy. The conducted survey did not show any significant change in the value of both effectiveness in the threshold, i.e. in 2015. The change occurred only in the slope of the regression line for cost effectiveness after 2015 for both procedures of its calculation.
Keywords: Registered Unemployment; Forms of Professional Activisation; Cost and Employment Effectiveness; Regression Discontinuity Design.